IMPLEMENTASI ADMINISTRASI KEPENDUDUKAN OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PONTIANAK MENGIKUTI MODEL GEORGE EDWARD III - Syarifah Sheila Raeditha E.01108001 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This thesis entitled "Implementation of the Regional Regulation No. 1 of 2008 on Population Administration By Department of Population and Civil Registration of Pontianak. This writing is intended to find out how the policy implementation of birth certificates in the department of population and civil registration of Pontianak. As for the background of this Thesis is based on the number of constraint problems during the manufacturing process of the birth certificates specifically on related institutions. The results of this study showed that policy implementation of birth certificates is not optimal. Communication between the implementor and people still do not work effectively, it is seen from there are still people who do not know the requirements in making a birth certificates, how much it costs, and how long it took to make them. The attitude of the staff of the Department of Population and Civil Registration of Pontianak is still lacking, it is seen from the weakness of officers in answering questions from the public relating to the birth certificates, but it is the accumulation of work by employees so that there is a retardation  time of completion  a birth certificates. The limited resource an obstacle in finish the job.Keywords: Implementation, Policy, Birth Certificates.